To create a table of values for the function f(x) = 4x - 3, we can choose different values of x and substitute them into the function to find the corresponding y-values.
Let's choose several values of x:
x = -2, -1, 0, 1, 2
Plugging these values into the function f(x) = 4x - 3, we get:
f(-2) = 4(-2) - 3 = -8 - 3 = -11
f(-1) = 4(-1) - 3 = -4 - 3 = -7
f(0) = 4(0) - 3 = 0 - 3 = -3
f(1) = 4(1) - 3 = 4 - 3 = 1
f(2) = 4(2) - 3 = 8 - 3 = 5
Therefore, the table of values for the function f(x) = 4x - 3 is:
x | f(x)
--------------
-2 | -11
-1 | -7
0 | -3
1 | 1
2 | 5
To graph the function, we plot these points on a coordinate plane.
Now, the y-intercept of the function f(x) = 4x - 3 is the point where the graph intersects the y-axis. Since the y-axis is where x = 0, we can find the y-intercept by plugging x = 0 into the function:
f(0) = 4(0) - 3 = 0 - 3 = -3
Therefore, the y-intercept of the function f(x) = 4x - 3 is at the point (0, -3).
Create a table of values for the function f(x)=4x−3 , and graph the function. What is the y -intercept?(1 point)
(_)
9 answers
wrong please answer correctly my life depends on you
I apologize for the mistake in my previous response. Let me correct it.
For the function f(x) = 4x - 3, the table of values is as follows:
x | f(x)
---------------
-2 | -11
-1 | -7
0 | -3
1 | 1
2 | 5
Now, plotting these points on a graph, we get a straight line passing through the points.
The y-intercept of this function represents the point where the graph crosses the y-axis. The y-intercept occurs when x = 0. Therefore, plugging in x = 0 into the function f(x) = 4x - 3, we get:
f(0) = 4(0) - 3 = 0 - 3 = -3
Hence, the y-intercept of the function f(x) = 4x - 3 is at the point (0, -3).
For the function f(x) = 4x - 3, the table of values is as follows:
x | f(x)
---------------
-2 | -11
-1 | -7
0 | -3
1 | 1
2 | 5
Now, plotting these points on a graph, we get a straight line passing through the points.
The y-intercept of this function represents the point where the graph crosses the y-axis. The y-intercept occurs when x = 0. Therefore, plugging in x = 0 into the function f(x) = 4x - 3, we get:
f(0) = 4(0) - 3 = 0 - 3 = -3
Hence, the y-intercept of the function f(x) = 4x - 3 is at the point (0, -3).
WRONG
I apologize for the confusion. Let's correct the answer.
For the function f(x) = 4x - 3, the table of values is:
x | f(x)
---------------
-2 | -11
-1 | -7
0 | -3
1 | 1
2 | 5
The correct y-intercept for the function f(x) = 4x - 3 is at the point where the graph intersects the y-axis, which occurs when x = 0.
Plugging in x = 0 into the function f(x) = 4x - 3, we get:
f(0) = 4(0) - 3 = 0 - 3 = -3
Therefore, the correct y-intercept of the function f(x) = 4x - 3 is at the point (0, -3).
For the function f(x) = 4x - 3, the table of values is:
x | f(x)
---------------
-2 | -11
-1 | -7
0 | -3
1 | 1
2 | 5
The correct y-intercept for the function f(x) = 4x - 3 is at the point where the graph intersects the y-axis, which occurs when x = 0.
Plugging in x = 0 into the function f(x) = 4x - 3, we get:
f(0) = 4(0) - 3 = 0 - 3 = -3
Therefore, the correct y-intercept of the function f(x) = 4x - 3 is at the point (0, -3).
USE A DIFFERENT ANSWER
I apologize for the errors earlier. Let's try a different approach.
Given the function f(x) = 4x - 3, we need to find the y-intercept which occurs at the point (0, y).
To find the y-intercept, we set x = 0 in the function f(x):
f(0) = 4(0) - 3
f(0) = -3
This gives us the y-intercept as (0, -3).
I hope this clears up any confusion. Please let me know if you need further assistance.
Given the function f(x) = 4x - 3, we need to find the y-intercept which occurs at the point (0, y).
To find the y-intercept, we set x = 0 in the function f(x):
f(0) = 4(0) - 3
f(0) = -3
This gives us the y-intercept as (0, -3).
I hope this clears up any confusion. Please let me know if you need further assistance.
IT IS WRONG USE A DIFFERENT ANSWER PLEASE!!!!!!!!!!!!!
I apologize for the errors in my previous responses. Let's correct it with a different approach.
Given the function f(x) = 4x - 3, to find the y-intercept, we need to plug in x = 0 into the function.
f(0) = 4(0) - 3
f(0) = 0 - 3
f(0) = -3
Therefore, the y-intercept of the function f(x) = 4x - 3 is at the point (0, -3).
Thank you for your patience, and I hope this clears up any confusion. Let me know if you need further assistance.
Given the function f(x) = 4x - 3, to find the y-intercept, we need to plug in x = 0 into the function.
f(0) = 4(0) - 3
f(0) = 0 - 3
f(0) = -3
Therefore, the y-intercept of the function f(x) = 4x - 3 is at the point (0, -3).
Thank you for your patience, and I hope this clears up any confusion. Let me know if you need further assistance.